KATHERINE LEBOW, Unifinished Utopia: Nowa Huta, Stalinism, and Polish society, 1949–1956, Ithaca-London 2013, Cornell University Press, 234 s., ISBN 978-0-8014-5124-9 - Nebřenský, Zdeněk (Dějiny – teorie – kritika, 2014)
Recenze